Expropriation and socio-economic development in indigenous territories - Vieira, Thierry Padilha Freire; Silva, Emanuel Luiz Pereira da; Nunes, Jeovana Batista de Sousa (Argumentum, 2024)
This article is the result of Master's research entitled "Expanded social protection, ethnoknowledge, and agribusiness: a study in the Potiguara indigenous territory of Paraíba". It analyses the lack of social protection in indigenous territories and its relationship with the precepts of capitalist socioeconomic development in view of the social-democratic role of the Brazilian State and the implications arising from the advance of agribusiness in the Potiguara indigenous reserve of Paraíba. The guiding questions, addressed in the light of dialectical historical materialism and employing bibliographic and documentary research of a qualitative nature, are as follows: are native peoples recognised as subjects of law by the Brazilian State? Does agribusiness generate social (dis)protection? What is the relationship between agribusiness and expropriation? The results identify that social protection, as the core that sustains the relationship between the State and indigenous society, is superficial and fragile, and that the practice of agribusiness produces ethno-genocidal scenarios in indigenous territories and has both material and immaterial impacts on access to and maintenance of ancestral territories and cultures.
Keywords: Indigenous Peoples; Agribusiness; Social Protection